2021
DOI: 10.5371/hp.2021.33.4.200
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive Protein Level, Admission to Intensive Care Unit, and High American Society of Anesthesiologists Score Affect Early and Late Postoperative Mortality in Geriatric Patients with Hip Fracture

Abstract: Purpose The main purpose of this study is to evaluate prognostic factors that affected the patients' early (<30 days) and late (six months, one year, and overall) postoperative mortality following hip fracture surgery. Materials and Methods This retrospective study included 515 patients older than 75 years old with surgically treated osteoporotic hip fracture. The demographic data, American Society of Anesthesiologists (ASA) classification, type of anesthesia, duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The lower early mortality amongst patients treated by orthogeriatric co-management care probably resulted from some different factors in some related literature [ 19 ]: First, the medical problems in long-lived patients are often of geriatric nature and are therefore better treated by geriatrist. Comorbidities like cerebrovascular or kidney disease and ICU admission were significant risk factors that increased mortality after osteoporotic hip fractures [ 33 , 34 ]. The orthogeriatric co-management care has greatly improved the level of comorbidity management, which can stabilize and improve the general condition of long-lived patients better and faster, avoid ICU admission, and then reduce the early mortality of long-lived elderly hip fracture patients.…”
Section: Discussionmentioning
confidence: 99%
“…The lower early mortality amongst patients treated by orthogeriatric co-management care probably resulted from some different factors in some related literature [ 19 ]: First, the medical problems in long-lived patients are often of geriatric nature and are therefore better treated by geriatrist. Comorbidities like cerebrovascular or kidney disease and ICU admission were significant risk factors that increased mortality after osteoporotic hip fractures [ 33 , 34 ]. The orthogeriatric co-management care has greatly improved the level of comorbidity management, which can stabilize and improve the general condition of long-lived patients better and faster, avoid ICU admission, and then reduce the early mortality of long-lived elderly hip fracture patients.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps due to the advancement of surgical techniques and the application of enhanced recovery after surgery (ERAS), these patients received better management for complications after surgery and enjoy a longer lifespan. Besides, the variable mortality reported in the literature may be associated with the heterogeneity of the population (i.e., age, co‐morbidities and national development) as well as postoperative care 21 . In Downey et al ., a retrospective analysis of local hip fracture cases from 36 different countries, the 1‐year mortality of patients was revealed as 2.4%–34.8% after a surgery for hip fractures 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the variable mortality reported in the literature may be associated with the heterogeneity of the population (i.e., age, co-morbidities and national development) as well as postoperative care. 21 In Downey et al, a retrospective analysis of local hip fracture cases from 36 different countries, the 1-year mortality of patients was revealed as 2.4%-34.8% after a surgery for hip fractures. 22 Another study demonstrated that the 5-year death rate was 21.1% in 221 patients (>70 years) with hip fractures who underwent selective surgery.…”
Section: Incidence Of Mortality After Ahamentioning
confidence: 99%
“…Identifying comorbidities using a score helps to understand the overall medical condition of the patient. [ 31 ] Kilic et al searched the existence of a comorbidity in their study and found that the ICU admission rate was 40.59% in the patient group without any comorbidity, whereas the ICU admission rate was found as 77.78% in the group with two comorbidities. [ 6 ] Accordingly, the increase of comorbidities caused a significant increase in the ICU admission rate postoperatively.…”
Section: Discussionmentioning
confidence: 99%